2012
DOI: 10.1364/boe.3.002190
|View full text |Cite
|
Sign up to set email alerts
|

Direct laser trapping for measuring the behavior of transfused erythrocytes in a sickle cell anemia patient

Abstract: Using a laser trap, we have studied the properties of erythrocytes from a sickle cell anemia patient (SCA) after receiving an intravenous blood transfusion, and a normal adult individual carrying normal adult hemoglobin. The hemoglobin type and quantitation assessment was carried out by high performance liquid chromatography (HPLC). We conducted an analysis of the size distributions of the cells. By targeting those erythrocytes in the overlapping regions of size distributions, we have investigated their proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Laser trapping has long been used to manipulate biological samples at the micron level [4,5]. However, to the best of our knowledge, it has never been used to study the ionization of a live cell in application of measuring the threshold radiation dose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser trapping has long been used to manipulate biological samples at the micron level [4,5]. However, to the best of our knowledge, it has never been used to study the ionization of a live cell in application of measuring the threshold radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, it has never been used to study the ionization of a live cell in application of measuring the threshold radiation dose. In our previous studies, we have used a high power laser trap to measure therapeutic efficacies in sickle cell anemia (SCA) disorder treatments [5]. During this process it was observed that a high power laser trap could ionize the human blood cells, effectively killing them, and eject them from the trap [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first time a laser tweezer (LT) was introduced by Ashkin [1] over three decades ago, it has been widely used for the micromanipulation of living objects for both biological and biomedical applications [2][3][4][5][6][7], as well as for nonliving objects to construct specific microstructures for optoelectronic applications [8]. An LT is an intensity gradient trap formed by focusing a highly collimated laser beam used to manipulate dielectric objects as small as an atom and as large as 100 micrometers by creating small forces in the order of piconewtons.…”
Section: Introductionmentioning
confidence: 99%
“…For nucleic acids, LTs have been used to mechanically unzip several thousand basepairs of DNA sequences in vitro [4], and measure unfolding/refolding kinetics of RNA [5]. The use of LTs in studying RBCs has also lead to some biomedical applications as reported by studies that use LTs to measure efficacies of therapies used to treat diseases affecting the mechanical properties of RBCs, such as sickle cell anemia [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is based on high intensity laser trapping of a single RBC. Laser trapping (LT) [2] techniques have been widely used to study the mechanical properties of RBCs [3,4]. In this study, we report our new procedure that demonstrates how individual RBCs can be charged, and the magnitude of the charge can be measured.…”
mentioning
confidence: 99%